1979
DOI: 10.1002/maco.19790300205
|View full text |Cite
|
Sign up to set email alerts
|

The high temperature corrosion resistance of α‐phase bronzes

Abstract: KurzfassungThe oxidation of Cu-Sn alloys containing up to 1 3 wt% Sn Die Oxidation von CuSn-Legierungen mit bis 13 Gew.-% in oxygen (1 atm) has been studied in the temperature range Zinn in puerstoff (1 atm) wurde im Fmperaturbereich 550 550 "Cto 800 "Cat 5 0 "Cintervals; the investigation involved the bis 800 C im Abstand von ieweils SO C untersucht; dabei study of the kinetics and of the morphology and structure of the scales by appropriate physical methods, with the aim o f correlating the two aspects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Another important observation of other scientists is that oxide layers consisting of cuprite and cassiterite with an outer layer of tenorite develop when tin bronzes are heated to temperatures of 300 C and above (Gesmundo et al 1979;Mathis, 2005, 76e94) (Fig. 13).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Another important observation of other scientists is that oxide layers consisting of cuprite and cassiterite with an outer layer of tenorite develop when tin bronzes are heated to temperatures of 300 C and above (Gesmundo et al 1979;Mathis, 2005, 76e94) (Fig. 13).…”
Section: Discussionmentioning
confidence: 95%
“…The fact that only few secondary corrosion products (i.e. malachite, azurite) are present in the browneblack patina indicates that these parts possessed a protective layer of copper and tin oxides before burial, thus, preventing severe natural alteration (Gesmundo et al 1979;Scott, 2002, 11;Piccardo et al 2007). Therefore, the dark patina has to be regarded as the original artificial corrosion layer that once perfectly contrasted with a yellowish and shiny metal colour of the stripes.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The presence of tin in alloy leads to a decrease in the oxidation rates; this is associated with the formation of tin oxide in the oxidation layer. Gesmundo et al [1] and Mathis et al [2] showed that tin in CuSn alloys does not form a continuous protective layer of tin oxide as can be the case in Cu -Zn alloy in which a ZnO protective layer is formed [3]. Rather, tin forms some precipitates in the oxide layer as Ni and Si form in the Cu -Ni [4] and Cu -Si [5] alloys respectively, which slows down the outward diffusion of copper.…”
Section: Introductionmentioning
confidence: 99%